Makna dan Nilai Budaya Melayu Studi Kasus pada Tari Zapin Melayu - Chanifudin Chanifudin (IAIN Syekh Nurjati Cirebon, 2023)
Zapin dance is one of the Malay cultural heritages on the Sumatra peninsula. Where in its development Zapin Dance develops following the characteristics of society based on the scope of culture. Zapin dance itself is one of the Islamic performing arts. Islamic performance art itself is an expression of the beauty of form from the side of the Islamic view of nature, life and humans that leads to a perfect meeting between truth and beauty. In its performances, Islamic performing arts tell and or describe the words and actions of the Prophet Muhammad SAW which are sourced from texts delivered in Arabic or local languages. This research focuses on the meaning and value of zapin dance itself. This type of research is library research with a grounded theory approach, namely through induction techniques to answer the focus with the support of evidence, theory development that has a fit with the immediate situation described, responsiveness aimed at context values. The results of the study indicate that zapin dance art which is full of movements symbolizes the values of Islamic teachings taught by the Prophet Muhammad, SAW in every detail of his movements, customary values and cultural values. The movement starts from alif, elbow tahto, elbow keluang, shut, rod point, cardinal directions. In addition, it is also a medium of information in carrying out the propagation of Islam, a symbol of social life, education, customs and as a symbol of tawhid faith in Allah SWT.